Diffuse large B-cell lymphoma: the curable disease? (Hematology Meeting Reports, 2009)
Diffuse large B-cell lymphoma (DLBCL) is the most common form of non-Hodgkin’s lymphoma (NHL), and accounts for around 30% of new cases. More than half of all patients with DLBCL can be cured with combination chemotherapy, but a substantial proportion of patients fail to respond. For around 30 years, the standard induction therapy for DLBCL has been the CHOP regimen of cyclophosphamide, doxorubicin, vincristine, and prednisone, given once every three weeks, typically for eight cycles. Recent research has resulted in a greater appreciation of the heterogeneity of patients with DLBCL and this has been defined by the International Prognostic Index (IPI) and gene microarray studies. Moreover, increased understanding of the molecular basis of DLBCL has supported the use of the anti-CD20 monoclonal antibody rituximab in combination with the CHOP regimen, which has led to improved response and survival in patients aged over 60 years. Such therapeutic effects have been demonstrated in two large phase III trials and a more recent trial in younger patients has indicated a similar benefit with the addition of rituximab, particularly in patients with a favourable prognosis. The use of dose-dense (2-weekly) CHOP chemotherapy has also delivered encouraging results in older patients. This approach is under investigation in younger patients with a poor prognosis, a group in which efforts to improve rates of 5-year survival have remained disappointing. As recent results obtained in older patients with DLBCL are the best achieved to date, CHOP in combination with rituximab has become the standard therapy against which other novel regimens should be compared. Intensification of chemotherapy with dose-dense 2-weekly CHOP also holds considerable promise.